P–451 Improving neovascularization and follicle viability in cryopreserved bovine ovarian tissue transplants. (6th August 2021) - Müller, A; Lehner, J; Hancke, K; Janni, W; Budschu, K
Abstract: Study question: Does cryopreservation and transplantation of bovine ovarian medulla-containing cortex tissue improve the viability and vascularization of the graft? Summary answer: Transplantation of bovine ovarian cortex containing medulla has a positive effect on follicular viability and neovascularization of the graft compared to cortex transplantation alone. What is known already: For female fertility protection, cryopreservation and retransplantation of ovarian tissue is a widely used method. During cryopreservation, ovarian tissue is exposed to mechanical and hypoxic stress resulting in follicular loss. Moreover, after retransplantation tissue vitality and follicle survival is limited due to ischemia. As follicular viability is of major importance for fertility and hormonal activity, the main focus is on improving vitality and viability of the grafts. In current protocols, ovarian medulla is discarded and merely cortex tissue is preserved. However, medulla tissue predominantly contains blood vessels, thereby obtaining high potential for revascularization processes and thereby supporting tissue vitality. Study design, size, duration: This experimental laboratory work was performed during a period of ten months. The rapidly vascularized chorioallantoic-membrane (CAM) of fertilized chicken eggs was used as model system to investigate neovascularization, follicle survival and tissue vitality of different bovine ovarian grafts. In four independent experimental rows four different tissue types (isolated cortex, thick medulla-containing cortex (8 x 10 x 3 mm), thin medulla-containing cortex (5 x 10 x 3 mm) and sole medulla tissue were compared. Participants/materials, setting, methods: Out of four bovine ovaries preserved from the slaughterhouse, in total 117 samples of the four different tissue types were primed and cryopreserved by the common slow-freezing protocol. After thawing, grafts were transplanted on separate CAMs at day four of fertilized eggs. After four days of incubation, blood vessels growing towards the grafts were counted. Subsequently, grafts were harvested, digested with collagenase and stained with Neutral Red® to determine the total amount of vital follicles. Main results and the role of chance: To investigate the neovascularization, all graft-supplying blood vessels were determined and distinguished between small and thick vessels. Compared to sole cortex, there were more small vessels in the medulla-containing grafts (9, 72 vs. 8, 65). Especially thin medulla- containing cortex pieces exhibited the highest number of small vessels (9, 90). Also in isolated medulla tissue an increased amount of small vessels was observed (9, 79). However, the average number of big vessels was not significantly different in all four test groups (Cortex: 2, 12; thin medulla-containing cortex: 1, 69; thick medulla-containing cortex: 1, 5; medulla: 2). The total number of all vessels differed from 10, 76 (sole cortex) to 11, 75 (medulla-containing grafts), indicating a support of neoangiogenesis by medulla tissue. To further examine whether medulla tissue also alters the amount of vital follicles, Neutral Red® stained vital follicles were determined in all different sample groups. Indeed, in medulla-containing cortex samples was an augmented average number of vital follicles (342, 4) compared to sole cortex tissue (256, 11). Most vital follicles were detectable in the thick medulla-containing cortex tissue (346, 61), closely followed by the thin medulla-containing cortex grafts (338, 19). As expected, there was just a rare amount of vital follicles in sole medulla grafts (8, 13). Limitations, reasons for caution: As the ovarian reserve in cattle is very individual, the prepared ovaries are different in their follicle amount. These individual differences may influence the number of counted follicles. Furthermore, the CAM model is only a short term experimental approach to investigate neovascularization and follicle survival. Wider implications of the findings: According to our results, transplantation of human medulla-containing cortex appears promising. Keeping medulla tissue on the graft seems to improve both follicle viability and revascularization. Our findings need to be proven with human tissue, but might change the preparation of human ovarian tissue for fertility preservation in future. Trial registration number: Not applicable